PENEGAKAN HUKUM TERHADAP AFFILIATOR TINDAK PIDANA PERJUDIAN ONLINE BERDASARKAN UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Novannisa Kharisma Kiki Herlinda; Dossy Iskandar Prasetyo (DE RECHT (Journal of Police and Law Enforcement), 2025)
This study aims to analyze law enforcement against affiliators involved in online gambling criminal acts under the Electronic Information and Transaction Law (ITE Law). Affiliators function as intermediaries between online gambling platforms and the public by exploiting social media to promote gambling activities on a large scale. This study also examines the obstacles encountered in the law enforcement process, including limited resources among law enforcement agencies, challenges posed by digital technology, and low levels of digital literacy within society, all of which contribute to high rates of public participation in online gambling. The method employed in this study is a normative juridical approach, involving the review of legislation, official documents, and relevant literature. Case analysis is also utilized to provide a concrete illustration of how the law is applied to online gambling affiliators. Based on the findings, Article 27 Paragraph 2 of the ITE Law serves as the primary legal basis for prosecuting affiliators who disseminate or facilitate access to gambling-related content. Nevertheless, obstacles such as limited digital forensic capabilities and difficulties in pursuing perpetrators across national borders remain the primary challenges in law enforcement. This study recommends strengthening the capacity of law enforcement agencies, particularly in the areas of digital technology and forensic investigation, as well as the need for cross-border cooperation to address international jurisdictional challenges. Through these measures, it is hoped that law enforcement against online gambling affiliators will become more effective and provide greater protection for the public from the adverse effects of online gambling.